2013
DOI: 10.1038/bmt.2013.106
|View full text |Cite
|
Sign up to set email alerts
|

Nailfold capillary abnormalities in sclerodermatous chronic GVHD

Abstract: Chronic GVHD (cGVHD) complicating allo-SCT commonly presents as sclerotic skin changes resembling systemic sclerosis (SSc), suggesting a common pathophysiological pathway. Damage to capillaries is considered an early event in the pathogenesis of SSc, and is associated with characteristic nailfold capillary abnormalities. Whether such nailfold capillary abnormalities occur in sclerodermatous cGVHD is unknown. Nailfold videocapillaroscopy (NVC) was used to evaluate capillary morphology, density and loop dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…They further showed that the endothelial microvasculature in chronic GVHD did not have the reduced VE cadherin and vWF expression observed in capillaries from patients with systemic sclerosis. Two related studies using capillaroscopy on nailfold capillaries confirmed the findings of Fleming et al that patients with PSS, but not chronic GVHD, had both morphologically abnormal capillaries and reduced density [100, 101]. …”
Section: Histological Criteria For the Diagnosis Of Gvhdmentioning
confidence: 56%
“…They further showed that the endothelial microvasculature in chronic GVHD did not have the reduced VE cadherin and vWF expression observed in capillaries from patients with systemic sclerosis. Two related studies using capillaroscopy on nailfold capillaries confirmed the findings of Fleming et al that patients with PSS, but not chronic GVHD, had both morphologically abnormal capillaries and reduced density [100, 101]. …”
Section: Histological Criteria For the Diagnosis Of Gvhdmentioning
confidence: 56%
“…Cutaneous cGvHD occurs in approximately half of patients who undergo allogeneic hematopoietic stem cell transplantation [34] and is typically assessed using histopathology [35,36]. Non-invasive imaging modalities, such as capillaroscopy, have been used to investigate cutaneous GvHD, with conflicting results [37,38] deeming it unsuitable [39]. High frequency ultrasound technology has also been used, but results were mixed for skin thickness measurements [40,41].…”
Section: Cutaneous Cgvhdmentioning
confidence: 99%
“…Cutaneous manifestations of systemic sclerosis (SS or scleroderma) are commonly associated with microvascular changes in the skin, previously visualized with capillaroscopy [45,46]. Microvascular injury is thought to precede the development of fibrotic tissue in SS [39]. Figure 7 compares the proximal nail folds of a healthy individual and a patient with SS.…”
Section: Systemic Sclerosis (Ss)mentioning
confidence: 99%
“…The fibrosis of the skin and internal organs observed in mice with Scl-GVHD results from the action of TGF-, PDGF, CTGF, FGF-1, EGF, and VEGF [129][130][131][132]. A study using nailfold capillaroscopy revealed that patients with Scl-GVHD present symptoms of vasculopathy, but to date, no data has been reported on mice [133]. With regards to therapeutics, several immunomodulatory drugs have been tested in these mice.…”
Section: Gvh-induced Systemic Sclerosismentioning
confidence: 97%